Analisis Balik Kestabilan Lereng Penambangan Batubara di PT Banjarsari Pribumi Site Banjarsari Kecamatan Merapi Timur, Kabupaten Lahat, Provinsi Sumatera Selatan - Romario Rahmad Radani; Yuliadi; Iswandaru (Bandung Conference Series: Mining Engineering, 2022)
Abstract. In this geotechnical analysis study the research uses the Limit Equilibrium Method (LEM) method to analyze single slopes and overall slopes. The input of material properties used comes from classification rock mass rating and the results of geotechnical mapping in the field which can also be applied for kinematic analysis on slopes that can represent other slopes to get the type of relaxation that can occur in the research area. Geotechnical analysis to be able to redesign slope geometry at PT Banjarsari Pribumi is based on the results of physical property tests, mechanical properties of rocks obtained from laboratory testing, and conducting geotechnical data in the field to be used as evaluation materials. The results of the overall slope stability analysis resulted in a cross-section of A-A' to a cross-section of G-G' and a single slope for waste material. Using new material properties and slope design it can be said that the slope is in a stable state or FK > 1.1 (Kepmen 1827). On the B-B' slope which is assumed to represent other slope conditions, kinematic analysis and potentially wedge avalanches.The overall slope stability analysis on the optimal lowwall slope has a slope height geometry design of 100 m, overall slope 290, bench width of 6 meters, bench height of 10 meters, and bench slope of 400, and interamp slope has a bench width of 13 meters. Abstrak. Dalam kajian analisis geoteknik ini penelitian menggunakan metode kesetimbangan batas atau Limit Equilibrium Method (LEM) untuk menganalisis lereng tunggal, lereng interamp dan lereng keseluruhan. Adapun input material properties yang digunakan berasal dari pengklasifikasian massa batuan (RMR) dan hasil pemetaan geoteknik (geotechnical mapping) di lapangan yang juga dapat di aplikasikan untuk dilakukannya analisis kinematik pada lereng yang dapat mewakili lereng lainnya sehingga mendapatkan jenis kelongsoran yang dapat terjadi pada daerah penelitian. Analisis geoteknik untuk dapat meredesain geometri lereng di PT Banjarsari Pribumi ini berdasarkan hasil uji sifat fisik, sifat mekanis batuan yang diperoleh dari pengujian laboratorium dan melakukan penggambilan data geoteknik di lapangan untuk dijadikan bahan evaluasi. Hasil analisis kestabilan lereng keseluruhan menghasilkan penampang A-A’ hingga penampang G-G’ dan lereng tunggal untuk material waste. Dengan menggunakan material properties dan desain lereng yang baru dapat dikatakan bahwa lereng dalam keadaan stabil atau FK > 1,1 (Kepmen 1827). Pada lereng B-B’ yang diasumsikan dapat mewakili kondisi lereng lain dilakukannya analisis kinematik dan berpotensi adanya longsoran baji. Analisis kestabilan lereng keseluruhan pada lereng bagian lowwall yang optimal secara teoritis memiliki desain geometri tinggi lereng 100 m, overall slope 290, lebar bench 6 meter, tinggi bench 10 meter dan kemiringan bench 400, serta lereng interamp memiliki lebar bench 13 meter.